2009
DOI: 10.1021/jm900110t
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Tetrasubstituted Imidazolines as Potent and Selective Neuropeptide Y Y5 Receptor Antagonists: Reduced Human Ether-a-go-go Related Gene Potassium Channel Binding Affinity and Potent Antiobesity Effect

Abstract: A series of novel imidazoline derivatives was synthesized and evaluated as neuropeptide Y (NPY) Y5 receptor antagonists. Optimization of previously reported imidazoline leads, 1a and 1b, was attempted by introduction of substituents at the 5-position on the imidazoline ring and modification of the bis(4-fluorphenyl) moiety. A number of potent derivatives without human ether-a-go-go related gene potassium channel (hERG) activity were identified. Selected compounds, including 2a, were shown to have excellent bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Although recent work done in mice demonstrated a very limited effect of NPY Y5R antagonism on GnRH neurons (49), it is possible there may be substantial species differences when it comes to NPY receptor pharmacology in rats and mice. The NPY Y5R antagonist-induced current in our studies reversed at − 85 mV, suggesting that the Y5R antagonist blocked activation of Kir or GIRK channels through the G i/o family of GPCRs (50, 51); these possibilities are currently being tested pharmacologically. Our results also showed that activation of GnRH neurons by blocking the Y5R required endogenous kisspeptin tone.…”
Section: Discussionmentioning
confidence: 67%
“…Although recent work done in mice demonstrated a very limited effect of NPY Y5R antagonism on GnRH neurons (49), it is possible there may be substantial species differences when it comes to NPY receptor pharmacology in rats and mice. The NPY Y5R antagonist-induced current in our studies reversed at − 85 mV, suggesting that the Y5R antagonist blocked activation of Kir or GIRK channels through the G i/o family of GPCRs (50, 51); these possibilities are currently being tested pharmacologically. Our results also showed that activation of GnRH neurons by blocking the Y5R required endogenous kisspeptin tone.…”
Section: Discussionmentioning
confidence: 67%
“…The resulting allenic products are direct precursors to 2,5-dihydrofurans with a pendant N (25,Scheme 1b) and allenyloxazolidinones (23,Scheme 1b), which are two key heterocycles in a diverse array of biologically active structures, fragrance compounds, antirheumatics and antidiabetics. 10,11 Diastereoselective methods to prepare oxazolidinones with pendant unsaturated moieties are severely limited, 12 and while the preparation of 2,5-dihydrofurans by Au-catalyzed cyclisation of allenes is well known, the same method to 2,5-dihydrofurans with pendant N are unknown -the only other routes involve long non-general multi-step synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Sato and colleagues generated an impressive chemical library of Y5‐selective antagonists still undergoing structural modifications, including arylpyrazole (Sato et al ., 2003) and xanthen derivaties (Sato et al ., 2008) and most recently a series of imidazoline derivaties (Sato et al ., 2009). On account of its high brain penetrability and access to plasma after oral administration, compound 2a was selected from a series of imidazoline‐derived Y5 antagonists (Sato et al ., 2009). Acute oral administration of 2a at a dose of 1 mg·kg −1 in Sprague‐Dawley rats induced an impressive 93% reduction in the food intake induced by the Y5 agonist D‐[Trp34]NPY (Sato et al ., 2009).…”
mentioning
confidence: 99%
“…On account of its high brain penetrability and access to plasma after oral administration, compound 2a was selected from a series of imidazoline‐derived Y5 antagonists (Sato et al ., 2009). Acute oral administration of 2a at a dose of 1 mg·kg −1 in Sprague‐Dawley rats induced an impressive 93% reduction in the food intake induced by the Y5 agonist D‐[Trp34]NPY (Sato et al ., 2009). Moreover, repeated four times daily for 5 days followed by twice daily for 15 days oral administration of up to 10 mg·kg −1 of 2a to weight stable diet‐induced obese mice led to a significant reduction in body weight (3 g on average) in wild‐type but not in Y5 −/− mice, despite comparable plasma levels of the compound in both genotypes.…”
mentioning
confidence: 99%
See 1 more Smart Citation